(untitled) (Global Journal of Medical Research, 2019)
This case study paper is written to raise awareness of prosthetic joint infection (PJI) of the right knee following periodontal debridement. The author understands that antibiotic prophylaxis for patients after the two-year post-operative milestone has been a topic of debate for over three decades. However, it is not like winning a lottery when a patient is in the small 2% of the knee prosthetic surgical population which develops a PJI. When prophylactic antibiotics and resistance to them are compared to the actual incidence of the PJI itself, costs cannot be restricted to the healthcare system, the source of income, and lack of mobility during recuperation, but should consider the patient’s quality of life and the state of mind during recuperation.